Percutaneous coronary intervention of unprotected left main stenoses - Procedural data and outcome depending on SYNTAX I Score - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2018)
BACKGROUND: We hypothesized that SYNTAX I score is a predictor for procedure complexity in left main PCI. Procedure complexity, duration and contrast load may contribute to adverse outcome of complex left main percutaneous coronary intervention (PCI). METHODS: In 105 consecutive patients who underwent PCI of unprotected left main coronary artery stenoses between 2014 and 2016, clinical parameters as well as PCI characteristics and follow-up data were analyzed. RESULTS: The mean SYNTAX I score was 29 ± 12, with 66 patients having a SYNTAX I score ≤ 32 and 39 patients a SYNTAX I score > 32. In patients with high SYNTAX I score vs. low-to-intermediate SYNTAX I score, single stent techniques were performed significantly less frequently (18% vs. 68%; p < 0.001), while Crush (44% vs. 5%; p < 0.001) and Culotte techniques (20% vs. 5%; p = 0.003) were performed significantly more frequently. Procedural success was achieved in all 105 cases without periprocedural mortality. During follow up, repeat PCI was necessary significantly more frequently in patients with high compared to patients with low-to-intermediate SYNTAX I score (34% vs.13%; p = 0.003). Nevertheless, overall mortality did not differ between patients with high vs. low-to-intermediate SYNTAX I score (20% vs. 18%). CONCLUSIONS: PCI strategies for the treatment of left main coronary artery stenoses get significantly more complex with increasing SYNTAX I scores. While this translates into a significantly longer procedure duration and contrast load, short-term outcome seems not to be influenced by the SYNTAX I score.
EVALuna2:213082